Analisis Kesiapan Mahasiswa dalam Menghadapi Program Pengalaman Lapangan pada Mahasiswa PGMI di FITK IAIN Surakarta - Saiful Islam; Pratiwi Rahmah Hakim; Dwi Muryani (Jurnal Simki Postgraduate, 2023)
The purpose of this study was to determine the readiness of PGMI IAIN Surakarta students in practicing the pedagogical, professional, personality, and ethical competencies of PPL students before carrying out practical field experiences. This research includes qualitative research and is descriptive-analytical. Data in this study were collected through interviews, documentation and questionnaires. The analytical model used is an interactive model of analysis. The readiness of students to do PPL at MI is obtained from microteaching to practice teaching skills. Future trainees will be able to practice real classroom teaching skills when they begin to teach at MI. Micro teaching is the right way to train prospective students to practice teaching competencies. In general, PGMI IAIN Surakarta study program students are very ready to carry out Field Experience Practice (PPL) in 2019. This is shown by data that 100% of PGMI IAIN Surakarta study program students belong to the very ready category.